Horticultural Plants Facing Stressful Conditions - Ways of Stress Mitigation - Hanaka, Agnieszka; Majewska, Małgorzata; Hawrylak-Nowak, Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are pleased to introduce this collection of research papers entitled "Horticultural Plants Facing Stressful Conditions - Strategies for Stress Mitigation". This reprint comprises twelve research papers and a review paper exploring the impact of stress factors on plant growth and ways to eliminate or mitigate them. The studies investigate various plant species, including sunflowers, zinnias, orchids, buttercups, tomatoes, snap beans, lettuce, jojoba, grapevines, strawberries and apple trees. The impact of stress caused by high temperatures, spring frosts, drought, salinity, copper and asbestos on the physiological, biochemical and anatomical changes in plants at the cellular, tissue, organ and whole-plant levels was described by the authors. The presented issues are crucial for comprehending the metabolic, molecular and genetic mechanisms underlying the enhancement of plant resistance to environmental stresses. This reprint focuses on three essential topics: (1) using exogenous compounds and bioinoculants to increase stress tolerance, (2) improving the quality and nutritional value of fruits and vegetables and (3) planting ornamental plants in polluted areas. Each paper has been meticulously prepared and contains figures, tables and a list of references to support a deeper understanding of the subject matter. In our opinion, this revised reprint will benefit scientists who are specifically interested in horticulture, plant physiology, biochemistry, microbiology and environmental sustainability.